AN ANALYSIS OF CODE-SWITCHING USED BY ENGLISH TEACHER IN SMA LAB UNDIKSHA - Elmiani, Ni Wayan Santi; Ramendra, Dewa Putu; Mahendrayana, Gede (International Journal of Language and Literature, 2019)
This study aimed at finding the type and the function of code-switching that is used by an English teacher in SMA Lab Undiksha. The data were collected through observation and interview. This study used the theory of Soewito, Poplack, and Hoffman to find the type of code-switching. This study use the theory of Mattson and Berenhult combined with Hall and Cook’s theory to find the function of code switching. The result of the study showed that four types of code switching were usually used by the teacher. There are 35 of Inter-sentential switching, 83 of intra-sentential switching, 29 of tag switching and 8 of internal code-switching. The functions for the use of code switching were 5 of topic switching, 23 of affective function and 127 of repetitive function.